Textural characteristics of mixed gels improved by structural recombination and the formation of hydrogen bonds between curdlan and carrageenan. (August 2022) - Tao, Haiteng; Guo, Li; Qin, Zhen; Yu, Bin; Wang, Yuxiao; Li, Jianpeng; Wang, Zhaobo; Shao, Xianbo; Dou, Guangpeng; Cui, Bo
Abstract: The physicochemical properties of a single gel are strongly affected by an admixture of another ingredient as a cosolvent. Although many studies have proposed the gelation mechanism of mixed gels using scattering, spectroscopic, thermal, and rheological techniques, direct evidence at the molecular scale is still lacking. As molecular models, carrageenan and curdlan are linear polysaccharides suitable for studying gelation mechanisms of mixed gels. In this study, based on texture profile analysis and fourier transform infrared spectroscopy, we divided mixed gels into three stages. In stage 1, carrageenan molecules were dispersed into the dissociated curdlan matrix and improved the curdlan gel network. In stage 2, the dissociated curdlan competed with carrageenan for water molecules preventing the formation of single gel or mixed gels, causing the decreased textural parameters. In stage 3, owing to structural recombination and the formation of hydrogen bonds between curdlan and carrageenan, a denser gel was formed. X-ray diffraction results showed that at curdlan: carrageenan ratios from 1:1–1:3, the crystalline peak of carrageenan appeared near 2 θ  = 28.5° and the peak of curdlan disappeared at 2 θ  = 19.5°, indicating that the dissociated curdlan destroyed the original crystalline domains of curdlan and dispersed into the carrageenan matrix. Scanning electron microscopic analysis revealed that at a curdlan: carrageenan ratio of 1:3, shorter and smaller junction zones facilitated a considerably more compact and dense structure. Based on molecular docking, curdlan was found to dissociate into a single helical chain, bonding with double- or single-helical carrageenan. Thus, structural recombination and new intermolecular hydrogen bonds between curdlan and carrageenan afforded considerably short and small junction zones. Graphical abstract: Image 1 Highlights: The shorter and smaller junction zones created a compacter and denser structure. Gel network strengthened via structural recombination and new hydrogen bonds. Gelation mechanisms were investigated with linear polysaccharides.